Age Requirement and Legal Certainty in Indonesia’s Presidential Candidacy after Decision No. 90/PUU-XXI/2023 - Abdul Hadi (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
This study examines the implementation of Law Number 7 of 2017 concerning General Elections, focusing on the minimum age requirement for presidential and vice-presidential candidates in Indonesia. The issue became significant after the Constitutional Court Decision Number 90/PUU-XXI/2023, which reinterpreted Article 169(q) to allow candidates under 40 years old to run if they currently hold or have held an elected public office. The research aims to analyze the legal certainty of this age limitation and its conformity with the principles of justice and equality enshrined in the 1945 Constitution. Using a normative juridical method, this study reviews relevant statutory provisions, legal doctrines, and academic commentaries to evaluate the consistency between the Court’s decision and constitutional values. The results reveal that the decision introduces a progressive shift in Indonesia’s constitutional jurisprudence by harmonizing formal legality with substantive justice. It ensures that legal certainty is maintained while promoting inclusiveness and equal opportunity in the democratic process. The conclusion emphasizes that the reinterpretation strengthens Indonesia’s constitutional democracy by affirming that leadership eligibility should be based on competence and public trust rather than age alone. This finding highlights the importance of integrating constitutional justice with democratic participation in future electoral law reforms.